1968
DOI: 10.4153/cjm-1968-091-3
|View full text |Cite
|
Sign up to set email alerts
|

An Axiomatic Line Geometry

Abstract: In their classic treatment (5) Veblen and Young build n-dimensional projective geometry from points and lines. Naturally, each line becomes identified with the set of points with which it is incident, and many treatments build from points alone, postulating the existence of certain distinguished subsets of the set of points. From either point of view, some labour is required, even in the two-dimensional case, to establish duality; hence a considerable interest attaches to self-dual systems of axioms; cf. (2; 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[19,4]; comp. also [1,22]). Assume that 1 = k = dim(V) − 1, since otherwise A is simply an affine space.…”
Section: 3 Structure Of Linear Complementsmentioning
confidence: 92%
See 1 more Smart Citation
“…[19,4]; comp. also [1,22]). Assume that 1 = k = dim(V) − 1, since otherwise A is simply an affine space.…”
Section: 3 Structure Of Linear Complementsmentioning
confidence: 92%
“…Thus the sets of the form S(a) are distinguished within C. 2For at least 3-dimensional affine spaces and for at least 4-dimensional projective spaces the result is well known as it is a result of a search for an adequate system of primitive notions for line geometry (cf [8,13,12,9,22]…”
mentioning
confidence: 98%
“…Sources for MLP financing typically include legal fellowships, federal, and state legal services dollars, project funding through Medicaid waivers, HRSA funding of Federally Qualified Health Centers (FQHCs), hospital community benefit dollars, administrative line items, and, in the academic space, universities. 58 A 2019 national environmental scan found that the median MLP budget is a paltry $100,000 annually, typically cobbled together from multiple sources, which supports a median of 1.0 FTE of attorney time and 0.2 FTE of support staff. 59 Because of unreliable funding, MLPs may operate with a skeleton legal staff, which disrupts programmatic integrity in the same way that other aspects of philanthropy-driven social services frequently are forced to survive on a grant-togrant, competitive basis.…”
Section: Filling In the "Last Mile" Of Mlp Operations So That Money F...mentioning
confidence: 99%
“…Pieri [15] first noted that projective three-dimensional space can be axiomatized in terms of lines and line-intersections. A simplified axiom system was presented in [7], and two new ones in [17] and [10], by authors apparently unaware of [15] and [7]. Another axiom system was presented in [16,Ch.…”
mentioning
confidence: 99%